Billy and the big new school - Anholt, Laurence; Anholt, Catherine (Morton Grove, Ill. : A. Whitman, 1999)
Billy is nervous about starting school, but as he cares for a sparrow that eventually learns to fly on its own, he realizes that he too can look after himself.
"Originally published in the U.K. by Orchard Books"--P. facing t.p.
Bulletin (Center for Children's books).
Publisher's Weekly.
School Library Journal.
2.2.
2.2
Keywords: Birds -- Fiction; First day of school -- Fiction; Schools -- Fiction; Birds -- Fiction; First day of school -- Fiction; School stories